Editorial: special issue “new insights into current and future vaccines against SARS-CoV-2 variants of concern and interest” - Qu, Bingqian; Li, Xue (Vaccines, 2023)
The coronavirus (COVID-19) pandemic has been a global threat for the past three years at the time of writing, leading to more than 675 million confirmed cases and 6 [...]